Intrathecal Clonidine versus Dexmedetomidine as Adjuvants to Hyperbaric Ropivacaine in Lower Limb Orthopaedic Surgeries: A Randomised Clinical Study - Priya Kishnani; Aiman Monaf; Kalpesh Pati; Jatin Patel; Sara Mary Thomas (Journal of Clinical and Diagnostic Research)
Introduction: Subarachnoid block is the most chosen mode for orthopaedic surgeries in lower limb. Adjuvants such as opioids and α2 agonists are often added intrathecally to improve or prolong the anaesthetic and analgesic effects. Ropivacaine, a novel local anaesthetic agent, is widely accepted as it has better safety profile as compared to bupivacaine and lignocaine. Aim: To compare clonidine and dexmedetomidine as adjuvants to hyperbaric ropivacaine given intrathecally in lower limb orthopaedic surgeries, focusing on haemodynamic changes, sedation, duration of analgesia, and sensory and motor blockades. Materials and Methods: This randomised clinical study was conducted in a teritary care facility at the Operation Theatre (OT) complex in the Department of Anaesthesiology at Dhiraj Hospital, Smt. Bhikhiben Kanjibhai Shah Medical Institute and Research Centre (SBKS and MIRC), Piparia, Waghodia, Vadodara, Gujarat, India. The study duration was 18 months, with a total sample size of 60 patients, comprising of 30 patients in each group. Group RC30 (Ropivacaine+Clonidine) was given 3.5 mL of 0.75% hyperbaric ropivacaine with 30 μg of clonidine, while Group RD5 (Ropivacaine + Dexmedetomidine) was given 3.5 mL of 0.75% hyperbaric ropivacaine along with 5 μg of dexmedetomidine, intrathecally. Results were assessed by comparing the onset and duration of sensory and motor blockade. The absolute and effective analgesia durations were also compared and side-effects and complications along with haemodynamic changes were analysed. Data was analysed using Statistical Package of Social Sciences (SPSS) Software version 26.0. Mean and Standard Deviation (SD) were derived for continuous variables and t-test or Analysis of Variance (ANOVA) was used to evaluate relationship between them, proportions for categorical variables and the Chi-square test was used for categorical variables. Results: The mean for age in Group RD5 was 39.43±10.6 years and Group RC30 was 41.43±13.65 years. The time to S2 regression was longer in Group RD5 (136.10±8.10 min) compared to Group RC30 (102.67±7.69 min) (p<0.0001). Longer duration of sensory and motor blockade was seen in Group RD5 (312.53±23.22 min, 381.40±30.01 min) as compared to Group RC30 (279.90±29.64 min, 321.63±38.82 min) (p<0.0001, respectively). Group RD5 also required fewer analgesic interventions in the first 24 hours. Absolute and effective analgesia was found longer in Group RD5 as compared to Group RC30 (p=0.0006, p=0.0022, respectively). Conclusion: Dexmedetomidine offers superior postoperative analgesia compared to clonidine but is associated with a higher incidence of bradycardia and hypotension, both of which are manageable with standard interventions.